TANTANGAN DAN STRATEGI IMPLEMENTASI LAYANAN SKCK ONLINE DI POLRES BENGKULU UTARA - Novia Kenitam Putra; Rosidin; Novlizah Eka parisia; Sri Indarti (Faculty of Social and Political Sciences Universitas Prof Dr Hazairin, SH, 2025)
The digitalization of public services is an essential component of bureaucratic reform aimed at improving efficiency, transparency, and accessibility for citizens. One of its implementations is the Online Police Clearance Certificate (SKCK) service, which has been introduced since 2018 at the North Bengkulu Police Resort (Polres Bengkulu Utara). This study aims to analyze the influence of assertive communication and active listening on marital relationship quality through enhanced emotional awareness and behavioral change. A qualitative case study approach was employed involving 8 informants-six married couples who had attended interpersonal communication training. Data were collected through in-depth interviews and analyzed using thematic analysis. The results indicate that assertive communication improves couples’ ability to express feelings and needs honestly without creating conflict, while active listening strengthens empathy, enhances mutual understanding, and fosters emotional intimacy. The combination of these skills contributes to healthier, more open, and respectful communication patterns. However, the study identified challenges such as persistent communication habits, resistance to change, and difficulty managing negative emotions. Future research is recommended to assess the long-term effectiveness of assertive communication training and to explore cultural factors influencing communication patterns in marital relationships.